KONSTRUKSI PEMIKIRAN TAFSIR NASR HAMID ABU ZAYD - Kamaruddin Mustamin (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2015)
This paper discusses the construction of interpretation thinking by Nasr Hamid Abu Zaid. He was a contemporary thinker who has a great interest in the study of the Qur'an. By study of literature, he argued that the text of the Qur`an always dialectic in populer context with the language 'muntaz tsaqafi' (cultural products). As Consequences, textual and socio-histories studies are necessary to the text of the Qur`an to get a correct understanding. On this basis, he said the Qur`an should be understood with the help of modern linguistic science including hermeneutic texts as others scripture. This kind of reading is not at all diminish the divinity of the Qur`an